Project-Based Module Development in the Electrical Circuit Course - Jean Dwi Ritia Sari; Ambiyar Ambiyar; Riki Mukhaiyar; Rizky Ema Wulansari (Jurnal Penelitian Pendidikan IPA, 2024)
Education is one of the efforts of awareness to realize cultural inheritance from past generations to new generations. Vocational education must prepare graduates who are easily absorbed by the industrial world and the business world, specifically for solving this problem, one solution is improving the learning model. The project-based learning model is able to form soft skills, gain knowledge to solve problems critically and creative thinking skills. The results of the research carried out were obtained, among other things, from each material validation statement, the experts stated that the module was valid and suitable for use. The results of media expert validation showed that the module was declared media valid. The response of lecturers in the electrical circuits course to the electrical circuits learning module gave a good response, namely the practicality level of the module was 78%, where the module was declared practical. A questionnaire distributed to students taking the Electrical Circuits course with 10 statements stated that the module received a score of 80%, where a score of 80% indicated that the module they used was practical for learning the Electrical Circuits course. The analysis carried out to see the results of the Paired T Test obtained a significant level of 0.000 < 0.05 which shows that there is a significant difference between the pretest and posttest results. It was concluded from this effectiveness test that there was a difference in the results before and after receiving treatment using Project-based Module Development in the Electrical Circuits Course.